Going Beyond the (Un)awakened Body: Arts-Based Collaborative Autoethnographic Inquiry of Korean Doctoral Students in the United States - Kang, Hyeungok; Lyu, Sung-Ryung; Yun, Sehyun (Journal of International Students, 2022)
Three Korean female doctoral students studying at U.S. higher education institutions address our lived experiences in this paper. By drawing on Critical Race Theory (CRT) and Asian Critical Theory (AsianCrit), we reflected upon the feelings and experiences that we swallowed to survive. We used collaborative autoethnography with artistic methods, such as digital collage and poetry, to share how we have wrestled with feelings of shame when reckoning our embodied knowledge of race and racism. Using CRT and AsianCrit, we disrupted racial stereotypes regarding Asians and their invisibility in racial discourses. We end with suggestions for providing support to Asian international students exploring racialized discourse and positioning themselves as qualified professionals and political agents. In sharing our stories, we hope to illuminate lived experiences that have been neglected, misunderstood, silenced, and forgotten.